2021
DOI: 10.1177/07316844211017646
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structural physiognomies of pawpaw fiber–glass fiber hybrid–based green composites on mechanical properties and biodegradation potential of epoxy composites

Abstract: The demand for durable and sustainable eco-friendly materials in recent times has caused many researchers to consider the use of plant fibers in composite development. In this research, the suitability of treated pawpaw fiber as a substitute for glass fiber was considered. The pawpaw fiber was extracted from the plant stem by dew retting and treated before been incorporated into the epoxy matrix. Two distinct fiber structures in linear and network forms were identified, separated, and used for the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Several natural fibres have been researched to improve the mechanical properties of reinforced and filled polymer bio-composites, including jute, banana, sisal, bagasse, bamboo, grass, flax, lufa, coir, cotton, wool, hair, feather, and many more [ 9 ]. However, recently in Nigeria, the more readily available natural fibers like pawpaw [ 10 ], banana, plantain, coconut, and sisal [ 2 , 11 ] from plants are being researched. The results from the studies revealed a potential use of these cellulosic fibers as reinforcement materials in polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Several natural fibres have been researched to improve the mechanical properties of reinforced and filled polymer bio-composites, including jute, banana, sisal, bagasse, bamboo, grass, flax, lufa, coir, cotton, wool, hair, feather, and many more [ 9 ]. However, recently in Nigeria, the more readily available natural fibers like pawpaw [ 10 ], banana, plantain, coconut, and sisal [ 2 , 11 ] from plants are being researched. The results from the studies revealed a potential use of these cellulosic fibers as reinforcement materials in polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Thin films, membranes, and fibers with 2D structures offer sufficient oxygen permeability, water resistance, and toughness. [ 112 ] On the other hand, sponges, foams, and hydrogels with 3D networks and porous structures can absorb large amounts of exudates, maintain a moist environment, and serve as vehicles for bioactive substances and cells. As such, the specific morphology of the biomaterials can determine their range of downstream applications.…”
Section: Classification Of Smart Hydrogelsmentioning
confidence: 99%
“…19 However, despite this abundance, pawpaw pant natural fibre is seldom employed as a reinforcing agent for lightweight materials, and there are limited studies on this subject in the existing literature. 20,21 Natural fibres, like pawpaw fibre, present numerous benefits, including their renewable nature, ability to biodegrade and lightweight properties. 22,23 Additionally, their accessibility and costeffectiveness render them an appealing substitute for synthetic reinforcements.…”
Section: Introductionmentioning
confidence: 99%